Pelatihan Literasi Informasi Berbasis Digital untuk Guru Sekolah Menengah - Marlini Marlini; Gustina Erlianti (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2020)
The aim of this community service program is for teachers to be able to use and utilize digital information resources optimally in supporting academic activities, publications and learning for schools and themselves. The training material covers how to utilize online databases, One Search, Google Scholar, Digital School Books (BSD), DOAJ, and registering to become a member of the RI National Library as a publication media and learning resource. Activities carried out by lecture, demonstration, direct practice and technical guidance methods. Participants are guided to register as library members, search for information or browse, and download the required information. Before the training activities began, PKM teams made a kind of pre-test for all participants to see the trainees' initial knowledge. From the pre-test results 99% of the trainees did not know the source of digital-based information. Evaluation is done by performing in searching information through an online database and downloading certain subject matter. From the results of this training, participants are expected to be able to utilize digital resources, browse and download subject matter and be able to publish writings through writing and articles. Another thing that needs to be underlined is that digital-based information literacy knowledge in vocational and high school teachers is still very limited and needs to be encouraged even more.